Continuous Synthesis of Hollow High‐Entropy Nanoparticles for Energy and Catalysis Applications. Issue 46 (5th October 2020) - Wang, Xizheng; Dong, Qi; Qiao, Haiyu; Huang, Zhennan; Saray, Mahmoud Tamadoni; Zhong, Geng; Lin, Zhiwei; Cui, Mingjin; Brozena, Alexandra; Hong, Min; Xia, Qinqin; Gao, Jinlong; et al.
Abstract: Mixing multimetallic elements in hollow‐structured nanoparticles is a promising strategy for the synthesis of highly efficient and cost‐effective catalysts. However, the synthesis of multimetallic hollow nanoparticles is limited to two or three elements due to the difficulties in morphology control under the harsh alloying conditions. Herein, the rapid and continuous synthesis of hollow high‐entropy‐alloy (HEA) nanoparticles using a continuous "droplet‐to‐particle" method is reported. The formation of these hollow HEA nanoparticles is enabled through the decomposition of a gas‐blowing agent in which a large amount of gas is produced in situ to "puff" the droplet during heating, followed by decomposition of the metal salt precursors and nucleation/growth of multimetallic particles. The high active sites per mass ratio of such hollow HEA nanoparticles makes them promising candidates for energy and electrocatalysis applications. As a proof‐of‐concept, it is demonstrated that these materials can be applied as the cathode catalyst for Li–O2 battery operations with a record‐high current density per catalyst mass loading of 2000 mA gcat. −1, as well as good stability and durable catalytic activity. This work offers a viable strategy for the continuous manufacturing of hollow HEA nanomaterials that can find broad applications in energy and catalysis. Abstract : The rapid and continuous synthesis of hollow high‐entropy‐alloy (HEA) nanoparticles by a "droplet‐to‐particle" nanomanufacturing method is reported. The formation of hollow HEA nanoparticles is enabled by the introduction of a blowing agent. The high active sites per mass ratio of such hollow HEA nanoparticles makes them promising candidates for electrocatalysis.